Assessment of Political Participation and Representation of Youths in the Politics of Ondo State, Nigeria (2003-2018) - Ayodele, Mustapha Haruna; Bayo, Enikanoselu; Toyyib, Musa (Unisia, 2024)
The research examined youths' participation and representation in politics and the decision-making process of Ondo State from 2003-2018. The available and existing literature shows that youth represent about half of Nigeria's population, just as in Ondo State. The research investigates the inverse relations of the youth population compared to leadership positions occupied in Ondo State, especially at the legislature and Executive levels in the years under study. The study adopts the theory of political participation as its theoretical framework for midwife work. In addition, the research methodology comprises both primary and secondary data, as the primary data is derived from interviews and survey research emphasizing the administration and analysis of a well-structured questionnaire. Statistics such as percentage representation, frequency table, and pictorial representation were also used. The research also examined the roles of environmental factors, youths' exorbitant behaviors, societal structures, and material facts that affect youths' political participation and representation in Ondo State and the nation at large. From a public policy perspective, the research study's findings provided veritable tools/insights for researchers, public policy analysts, Electoral agencies/reformers, political parties, politicians, and Nigeria in the quest for Youth involvement in politics and leadership positions. Equally, the outcome of the research study enhanced future research work and discourse on democracy, youth participation, and representation in Ondo State, in particular, and Nigeria in general.